Pseudotumor as adverse local tissue reaction due to implant corrosion - Vukadin, Ognjen B.; Džudović, Jelena M.; Repić, Aleksandra M.; Baščarević, Zoran Lj. (Vojnosanitetski pregled, 2023)
Introduction. The term adverse local tissue reactions (ALTRs) is used to describe pathologic tissue conditions appearing after total joint replacement, and it includes osteolysis, bone necrosis, muscle necrosis, cystic lesions, excessive fluid collections, soft tissue masses, pseudotumors, metal sensitivity, metallosis, and chronic inflammatory lesions. ALTRs are rarely described in the literature after the breakage of the ceramic components of the hip prosthesis. Case report. We present a case of a patient with massive fluid collections filled with metallic and tissue detritus, along with signs of systemic cobalt (Co) and chromium (Cr) intoxication. Symptoms developed after revision of the acetabular component with the application of a metal-on-polyethylene coupling. Previously, several revisions were made due to breakage of the ceramic components of the endoprosthesis and instability of the hip. After removal of pseudotumor masses and revision of all components of the endoprosthesis with implantation of a coupling between the ceramic head and the polyethylene insert, there was a significant drop in the serum values of Co and Cr. Conclusion. Trunnion damage should be assessed during revision procedures, and if present, both prosthetic components should be replaced to prevent disastrous effects of metallic corrosion, ALTRs, and systemic metallic ions intoxication. Measurement of serum levels of Co and Cr in patients after joint replacement could identify patients at risk for the development of ALTRs and metallosis.